TINGKAT DEPRESI MAHASISWA YANG SEDANG MENYUSUN SKRIPSI DI FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA TAHUN 2019 - Surya Dewi, Ni Made Betti Ratricia; Subrata, I Made; Kardiwinata, Made Pasek; Ekawati, Ni Komang (ARCHIVE OF COMMUNITY HEALTH, 2019)
ABSTRACT Depression is a mental disorder characterized by a decrease in mood, feelings of guilt and withdrawal from social life. Depression can occur in all age groups including students. Research conducted at Medical Faculty of Muhammadiyah in North Sumatra found that students who depressed in compiling thesis were 23.80%. The high prevalence of depression, as well as the lack of research related to this in Medical Faculty, Udayana University, shows that this research is important.This research aims to determine the level of depression of students in Medical Faculty, Udayana University who compiled thesis. Design of this study was descriptive cross sectional. Sample in this study were 80 students who were measured using the BDI II questionnaire. Results showed that 27.50% of students who compiling thesis at the Medical Faculty of Udayana University had mild depression, 11.25% had moderate depression. These results indicate that the prevalence of depression in students who compiling thesis is quite high. Therefore, preventive and promotive planning is needed to reduce the prevalance of depression in students. Keywords : Depression, Mini Thesis, Medical Student